Analisis SWOT sebagai Strategi Pemasaran Pupuk Organik Cair dari Limbah Dapur (Kulit Buah) di Kelurahan Urangagung, Kabupaten Sidoarjo - Widia Safitri, Dinda Ayu (abdimesin, 2025)
Currently, UMKM have become a special focus for the government, with strong support for their development. The community in Urangagung Village, Sidoarjo District, Sidoarjo Regency, primarily engaged in farming, has the opportunity to establish and develop UMKM through the idea of liquid organic fertilizer products. Utilizing kitchen waste, such as fruit peels, can create high economic value. Development and innovation are needed to sustain and expand this business. SWOT analysis is used to identify the strengths, weaknesses, opportunities, and threats in business development. Through this analysis, strategies can be devised to address challenges, seize market opportunities, and maintain competitiveness. Product promotion, market research, and improvements in product quality and technology are key elements in developing the liquid organic fertilizer business. Thus, these UMKM can not only survive but also thrive on a larger scale.